2013
DOI: 10.1517/14712598.2013.823153
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived stem cells in clinical applications

Abstract: ASCs seem to be the perfect tool for regenerative medicine and immunosuppressive cellular therapies. Nevertheless, there are some tasks that should be addressed by the future studies: i) ASCs require better characterisation; a set of markers determining ASCs should be clearly defined; ii) there is need for more studies on safety of reconstructive therapies with ASCs in cancer patients (e.g., after mastectomy); iii) release criteria should be determined for freshly isolated and ex vivo expanded ASCs designed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 91 publications
0
59
0
2
Order By: Relevance
“…The hASCs were selected for this study due to their multipotency and ability to differentiate into various lineages 42,43 . Adipose tissue is an abundant source of autologous adult stem cells, which may be implicated in variety of cell-based therapies for the regeneration of acute and chronically damaged tissues 44,45 . To ensure that developed injectable hydrogels, reinforced with a-CNCs have preferential cell supportive properties we tested the ability of hASCs to adhere on the surface of produced nanocomposites and HAX.…”
Section: Cellular Interactions With Ha-cncs Hydrogelsmentioning
confidence: 99%
“…The hASCs were selected for this study due to their multipotency and ability to differentiate into various lineages 42,43 . Adipose tissue is an abundant source of autologous adult stem cells, which may be implicated in variety of cell-based therapies for the regeneration of acute and chronically damaged tissues 44,45 . To ensure that developed injectable hydrogels, reinforced with a-CNCs have preferential cell supportive properties we tested the ability of hASCs to adhere on the surface of produced nanocomposites and HAX.…”
Section: Cellular Interactions With Ha-cncs Hydrogelsmentioning
confidence: 99%
“…SVF isolates typically contain many components also found in adipose tissue including adipocytes, fibroblasts, preadipocytes, tissue resident macrophages, and vascular constituents (Baer and Geiger 2012; Aronowitz and Ellenhorn 2013; Gimble et al 2011). Most importantly, both adipose tissue and SVF provide a source of mesenchymal stem cells (MSCs) that do not elicit an immunological response, particularly if autologous ASCs are used during point-of-care applications (McIntosh et al 2009; Pikuła et al 2013). Of the three main sources of MSCs currently used for human studies and therapies—bone marrow, umbilical cord blood, and adipose tissue—ASCs show important differences from bone-marrow derived MSCs in regard to harvest and cell yield, despite similarities in morphology and phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose-derived stem cells (ASCs) proved to have significant biological properties and considerable therapeutic potential [71]. It seems that ASCs, in their physiological state, remain rather quiescent, but under stimulation (such as a wound, a transplant, or in vitro culture) exert pro-regenerative capabilities.…”
Section: Cell Therapies For Chronic Wound Treatmentmentioning
confidence: 99%
“…ASCs are a promising tool for treatment of chronic (e.g. ulcers) and oncological wounds [71]. Riggotti et al [77] in a pilot clinical study in humans showed that injection of autologous lipopaspirates, which contain ASCs, can be effective in treating late side effects of radiotherapy.…”
Section: Cell Therapies For Chronic Wound Treatmentmentioning
confidence: 99%